Essays on economic development and regional economic inequalities with a focus on Southern European countries - Barros, Diana (2021)
Income inequality within and among countries is a persistent concern and a central issue in the studies devoted to economic development. The literature on regional income inequality is scant but it is on the rise. Despite recent research dynamics, a comprehensive exploration of the determinants of regional income inequality has yet to be accomplished. Moreover, a context-dependent analysis of regional inequality is advisable given the importance of the structural features that underlie regional inequalities. This thesis seeks to address the determinants that govern regional income inequality and to pursue a context-dependent analysis focusing on the case of Southern European regions, in comparison to Northern European regions. Departing from this general objective, the following specific objectives were outlined: (a) to present a comprehensive, quantitative (bibliometric) account of the indexed scientific literature on economic development, scrutinising the scientific attention devoted to regional income inequality; (b) to propose a novel theoretical framework that seeks to explain the main mechanisms through which regional income inequality emerges; (c) to empirically assess which are the most significant and/or frequently mentioned determinants of regional income inequality; and (d) to empirically assess whether regional income determinants differ in significance and magnitude between the Southern European regions and Northern European regions. The thesis consists of four essays that work both as independent and interrelated studies. The results indicate that insufficient attention has been paid to Southern European countries on matters related to regional income inequalities and regional development. Additionally, a clear divide between Southern and Northern European regions has been uncovered in terms of the determinants of regional income inequality, particularly at the institutional policy level. The institutional policy factors, namely increased local government expenditures devoted to social transfers, tend to significantly mitigate regional income inequality in both Southern and Northern European regions, but with greater impact on the latter. The findings contribute to guide future policy actions aimed at curbing income inequalities at the regional level.